Analysis of deformation rule of deep foundation pit excavation of railway station in soft soil with silt - Weijian Liu; Zhonghe Wang; Zhizeng Zhang; Zhengyu Zhang; Yongfu Jia; Zhun Li (Scientific Reports)
Abstract This study investigates the behavior of retaining structures and the settlement of external surfaces in deep foundation pits located in areas characterized by muddy soft soil. The research evaluates the efficacy of two constitutive models—the traditional Mohr-Coulomb model and the modified Cambridge model—during the simulation of foundation pit excavation. By analyzing actual monitoring data collected from the site, the study identifies patterns in the settlement and deformation of both the retaining structure and the surface. Subsequently, the excavation process of the foundation pit is simulated using FLAC3D 6.0 software, employing both the Mohr-Coulomb and modified Cambridge models. A comparative analysis is conducted between the simulation results and the field monitoring data to assess the performance of the two models.The findings indicate that the horizontal displacement and surface settlement curves of the retaining structure in muddy soft soil exhibit cantilever behavior. The maximum horizontal displacement occurs near the excavation face, while the peak surface settlement is observed 15 m from the foundation pit, remaining within the established early warning thresholds. Although both models demonstrate a similar trend in the simulated displacement curves compared to the actual deformation curves, there are notable differences in accuracy. Specifically, the modified Cambridge model generally exhibits a lower error rate in simulating the horizontal displacement of the retaining structure compared to the traditional Mohr-Coulomb model. Furthermore, the modified Cambridge model provides a closer approximation to the measured values for surface settlement outside the foundation pit.In conclusion, for deep foundation pits associated with subway construction that utilize concrete support and underground continuous walls in muddy soft soil regions, the horizontal displacement and surface settlement curves of the retaining structure display cantilever characteristics. The modified Cambridge model demonstrates superior simulation performance, yielding results that are more closely aligned with actual monitoring data.